Welche Wachstumspotenziale lassen sich über das Arbeitsangebot erschließen? - Joachim Möller (Wirtschaftsdienst, 2017)
– Demographic change will lead to a shrinking and ageing population in Germany, resulting in a decrease in the labour force. The fundamental trend can be counteracted through net immigration and behavioural effects such as increasing labour market participation of females in the short and medium run, but is unlikely to be reversed in the long run. This paper shows that the average age of the labour force follows a linear trend since the late 1990s. Moreover, there has been a convergence of average age between male and female workers. In a long run perspective the age distribution has become less heterogeneous, as measured by the coeffi cient of variation. At the same time, the average length of schooling and training has increased signifi cantly over the last 40 years, but at a slower pace in recent years. We discuss the consequences of these changes for economic growth.
Keywords: J11; J21; J24; 330